Périodisation sociolinguistique de la lexicographie dialectale niçoise - Philippe Del Giudice (Lengas)
The dialectal lexicography of Nice is more than 150 years old. It consists of a multitude of lexicons, of which very few are distinguished by their originality. Still, a periodization of the corpus is possible – and enlightening – if it is based on the features that reflect the very particular social context of Niçois. The analysis of several dictionaries at different levels (metalanguage and linguistic combination; graphic system; sources; handling of the dialectal characteristics of Niçois) leads to the identification of three distinct periods which reveal how Niçois dialect speakers have questioned their identity over time.